Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the position function [tex]\( s(t) \)[/tex] given the velocity function [tex]\( v(t) = e^{-3t} + 3 \)[/tex] and the initial position [tex]\( s(0) = 2 \)[/tex], we need to follow these steps:
1. Understand the Relationship Between Velocity and Position:
The velocity function [tex]\( v(t) \)[/tex] is the derivative of the position function [tex]\( s(t) \)[/tex]. Thus, we have:
[tex]\[ v(t) = \frac{ds}{dt} \][/tex]
We need to integrate the velocity function to obtain the position function.
2. Integrate the Velocity Function:
To find [tex]\( s(t) \)[/tex], we integrate [tex]\( v(t) \)[/tex] with respect to [tex]\( t \)[/tex]:
[tex]\[ s(t) = \int v(t) \, dt \][/tex]
Substituting the given velocity function [tex]\( v(t) \)[/tex]:
[tex]\[ s(t) = \int (e^{-3t} + 3) \, dt \][/tex]
3. Performing the Integration:
We integrate the function [tex]\( e^{-3t} + 3 \)[/tex] term by term:
[tex]\[ s(t) = \int e^{-3t} \, dt + \int 3 \, dt \][/tex]
- First Term: Integrating [tex]\( e^{-3t} \)[/tex]:
[tex]\[ \int e^{-3t} \, dt = -\frac{1}{3} e^{-3t} + C_1 \][/tex]
where [tex]\( C_1 \)[/tex] is a constant of integration.
- Second Term: Integrating [tex]\( 3 \)[/tex]:
[tex]\[ \int 3 \, dt = 3t + C_2 \][/tex]
where [tex]\( C_2 \)[/tex] is a constant of integration.
Combining both terms, we get:
[tex]\[ s(t) = -\frac{1}{3} e^{-3t} + 3t + C \][/tex]
where [tex]\( C = C_1 + C_2 \)[/tex] is the combined constant of integration.
4. Determine the Constant of Integration with Initial Condition:
We use the initial condition [tex]\( s(0) = 2 \)[/tex] to find the constant [tex]\( C \)[/tex]:
[tex]\[ s(0) = -\frac{1}{3} e^{0} + 3(0) + C = 2 \][/tex]
Simplifying:
[tex]\[ -\frac{1}{3} + C = 2 \][/tex]
Solving for [tex]\( C \)[/tex]:
[tex]\[ C = 2 + \frac{1}{3} = \frac{6}{3} + \frac{1}{3} = \frac{7}{3} \][/tex]
5. Write the Final Position Function:
Substituting [tex]\( C = \frac{7}{3} \)[/tex] back into the position function, we have:
[tex]\[ s(t) = -\frac{1}{3} e^{-3t} + 3t + \frac{7}{3} \][/tex]
Simplifying, we can write the final position function as:
[tex]\[ s(t) = 3t + \frac{7}{3} - \frac{e^{-3t}}{3} \][/tex]
So, the position function [tex]\( s(t) \)[/tex] is:
[tex]\[ s(t) = 3t + 2 - \frac{e^{-3t}}{3} \][/tex]
1. Understand the Relationship Between Velocity and Position:
The velocity function [tex]\( v(t) \)[/tex] is the derivative of the position function [tex]\( s(t) \)[/tex]. Thus, we have:
[tex]\[ v(t) = \frac{ds}{dt} \][/tex]
We need to integrate the velocity function to obtain the position function.
2. Integrate the Velocity Function:
To find [tex]\( s(t) \)[/tex], we integrate [tex]\( v(t) \)[/tex] with respect to [tex]\( t \)[/tex]:
[tex]\[ s(t) = \int v(t) \, dt \][/tex]
Substituting the given velocity function [tex]\( v(t) \)[/tex]:
[tex]\[ s(t) = \int (e^{-3t} + 3) \, dt \][/tex]
3. Performing the Integration:
We integrate the function [tex]\( e^{-3t} + 3 \)[/tex] term by term:
[tex]\[ s(t) = \int e^{-3t} \, dt + \int 3 \, dt \][/tex]
- First Term: Integrating [tex]\( e^{-3t} \)[/tex]:
[tex]\[ \int e^{-3t} \, dt = -\frac{1}{3} e^{-3t} + C_1 \][/tex]
where [tex]\( C_1 \)[/tex] is a constant of integration.
- Second Term: Integrating [tex]\( 3 \)[/tex]:
[tex]\[ \int 3 \, dt = 3t + C_2 \][/tex]
where [tex]\( C_2 \)[/tex] is a constant of integration.
Combining both terms, we get:
[tex]\[ s(t) = -\frac{1}{3} e^{-3t} + 3t + C \][/tex]
where [tex]\( C = C_1 + C_2 \)[/tex] is the combined constant of integration.
4. Determine the Constant of Integration with Initial Condition:
We use the initial condition [tex]\( s(0) = 2 \)[/tex] to find the constant [tex]\( C \)[/tex]:
[tex]\[ s(0) = -\frac{1}{3} e^{0} + 3(0) + C = 2 \][/tex]
Simplifying:
[tex]\[ -\frac{1}{3} + C = 2 \][/tex]
Solving for [tex]\( C \)[/tex]:
[tex]\[ C = 2 + \frac{1}{3} = \frac{6}{3} + \frac{1}{3} = \frac{7}{3} \][/tex]
5. Write the Final Position Function:
Substituting [tex]\( C = \frac{7}{3} \)[/tex] back into the position function, we have:
[tex]\[ s(t) = -\frac{1}{3} e^{-3t} + 3t + \frac{7}{3} \][/tex]
Simplifying, we can write the final position function as:
[tex]\[ s(t) = 3t + \frac{7}{3} - \frac{e^{-3t}}{3} \][/tex]
So, the position function [tex]\( s(t) \)[/tex] is:
[tex]\[ s(t) = 3t + 2 - \frac{e^{-3t}}{3} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.